Steel structure surface water-based recoatable low-surface-energy coating and preparation method thereof
By using formulas composed of aqueous silicon sol, acrylic resin, modified anti-rust pigment and low-surface energy additives on the surface of the steel structure, the shortcomings of existing water-based coatings in low surface energy and recoating properties are solved, and coatings with high adhesion, good anti-rust performance and self-cleaning properties are achieved, and the service life of the steel structure is extended.
Patent Information
- Application Number
- CN202510316622.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing water-based coatings still need to be improved in terms of low surface energy and recoating properties, and it is difficult to effectively protect the steel structure from corrosion and pollution.
The formula consisting of aqueous silicon sol, acrylic resin, modified anti-rust pigment, low-surface energy additives, etc. is used to form a coating with excellent weather resistance, rust resistance, adhesion and low-surface energy characteristics through reasonable proportioning and preparation processes.
It achieves high adhesion, good rust resistance and self-cleaning properties of the paint, can effectively extend the service life of the steel structure, and has good recoating and environmental protection properties.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating preparation, and relates to a water-based recoatable low-surface-energy coating for a steel structure surface and a preparation method thereof. Background Art
[0002] With the development of industry, steel structures are increasingly used in buildings, bridges, offshore platforms and other fields. However, steel structures are exposed to the natural environment for a long time and are easily corroded by various factors such as atmospheric corrosion and chemical corrosion, which shortens their service life. Therefore, it is of great significance to effectively protect steel structures. Traditional anti-corrosion coatings for steel structures are mostly solvent-based coatings, which contain a large amount of volatile organic compounds (VOCs), which not only pollute the environment, but also pose a threat to the health of construction workers. Water-based coatings have gradually become a research hotspot due to their advantages such as environmental protection, safety, and energy saving. At present, water-based coatings on the market still need to be improved in terms of low surface energy and recoatability. Therefore, it is of great practical significance to develop a high-performance water-based recoatable low surface energy coating. Summary of the invention
[0003] The purpose of the present invention is to provide a water-based recoatable low surface energy coating for the surface of a steel structure and a preparation method thereof, which has the characteristics of good hydrophobicity, strong rust resistance, high adhesion and strong tolerance.
[0004] The purpose of the present invention can be achieved by the following technical solutions: A water-based recoatable low surface energy coating for the surface of a steel structure, wherein the coating has the following formula, by weight, 10 to 30 parts of water-based silica sol, 70 to 90 parts of acrylic resin, 10 to 20 parts of modified anti-rust pigment, 1 to 2 parts of dispersant, 0.1 to 0.5 parts of defoamer, 0.5 to 1 parts of leveling agent, 0.5 to 1 parts of low surface energy additive, and 10 to 20 parts of deionized water; Wherein, the mass ratio of aqueous silica sol to acrylic resin is (1-3): (7-9); The modified anti-rust pigment is prepared by dispersing mica iron oxide, aluminum tripolyphosphate and bismuth molybdate in a fluorocarbon resin and a methacrylic resin in a volume ratio of 2:1; The low surface energy auxiliary agent is prepared by mixing perfluoroalkyl ethanol, perfluoroalkyl acrylate, hydrogen fluorine silicone oil, dimethyl sulfoxide and ammonium persulfate.
[0005] Furthermore, the specific preparation method of the modified anti-rust pigment is as follows: S2.1: Micaceous iron oxide, aluminum tripolyphosphate and bismuth molybdate are mixed in a mass ratio of 1:1:(0.5-1), and ground in a ball mill at a speed of 400 r / min for 0.5-1 h to obtain a mixture A; S2.2: fluorocarbon resin and methacrylic resin were mixed in a volume ratio of 2:1, and stirred at a speed of 200 r / min for 0.5 h to obtain a mixed resin B; S2.3: Disperse mixture A in mixed resin B with a solid-liquid mass ratio of 1:2, stir at a speed of 400 r / min for 0.5 h, then add 1 wt% polyethylene glycol 2000 and 1 wt% silane coupling agent KH550, continue stirring for 0.5 h, filter the mixture with a gauze to obtain the modified anti-rust pigment.
[0006] Furthermore, the dispersant is one or more of hydroxymethyl cellulose, polyethylene oxide, and polyvinyl alcohol.
[0007] Furthermore, the defoaming agent is one or more of diethanolamine, isopropanol, and lauroyl isopropanolamine.
[0008] Furthermore, the leveling agent is one of GLIDE 450W and GLIDE 411.
[0009] Furthermore, the preparation method of the low surface energy additive is as follows: Under stirring at a speed of 200 r / min, perfluoroalkylethanol and perfluoroalkylacrylate are mixed in a mass ratio of 1:1, 3wt% of hydrogen-containing fluorosilicone oil is added to the mixture to obtain a mixture C, and the mixture C is dispersed in dimethyl sulfoxide, the volume ratio of the mixture C to dimethyl sulfoxide is 1:2, and stirring is continued. While stirring, ammonium persulfate is slowly added at a rate of 2s / drop, wherein the mass ratio of the added ammonium persulfate to the perfluoroalkylacrylate is 1:20. After the addition is completed, stirring is continued at room temperature for 10 minutes, and then the temperature is slowly increased to 90-110°C at 2°C / min under stirring, and the reaction is carried out for 6-8 hours after the constant temperature. After the reaction is completed, the mixture is allowed to stand and the temperature is cooled to room temperature to obtain the low surface energy additive.
[0010] Furthermore, the particle size of the mixture A in S2.1 is 400 mesh.
[0011] Furthermore, a 300-mesh gauze is used for filtering in S2.3.
[0012] A method for preparing a water-based recoatable low surface energy coating for a steel structure surface. The specific process of the method for preparing the water-based recoatable low surface energy coating is as follows: S9.1: Add deionized water into a dispersion tank, add dispersant, defoamer and modified anti-rust pigment in order according to the formula ratio under stirring at a speed of 300 r / min, stir for 10 minutes, and then perform high-speed dispersion treatment at a speed of 1500-2000 r / min for 20-30 minutes to obtain a base material; S9.2: Slowly add the aqueous silica sol to the base material, stir at a speed of 300 r / min, stir for 10 to 20 minutes, add acrylic resin, leveling agent and low surface energy additive, continue stirring for 1 to 2 hours, and obtain the aqueous recoatable low surface energy coating.
[0013] Furthermore, the base material fineness obtained by dispersion in S9.1 is less than 30 μm.
[0014] In the formula of the present invention, water-based silica sol is used as one of the key components of the coating, and its main function is to enhance the weather resistance, hardness and wear resistance of the coating. The silicon dioxide particles in the silica sol can form a dense network structure in the coating, effectively improving the physical protection ability of the coating and resisting the erosion of the external environment. At the same time, the silica sol also has a certain self-cleaning function, which can reduce the adsorption of pollution on the surface of the coating and keep the coating clean and beautiful; acrylic resin, as the main film-forming substance of the coating, plays a decisive role in the overall performance of the coating. It not only gives the coating good adhesion and glossiness, but also ensures the flexibility and chemical resistance of the coating. The excellent film-forming properties of acrylic resin enable the coating to fit closely to the surface of the steel structure, forming a continuous and uniform protective layer, effectively isolating the penetration of corrosive media such as moisture and oxygen, thereby extending the service life of the steel structure; the modified anti-rust pigment plays a key anti-rust role in the coating. The anti-rust pigment modified by chemical and physical means can be more effectively combined with the coating matrix to form a dense anti-rust barrier, preventing the corrosive medium from directly contacting the steel structure, thereby significantly improving the anti-rust performance of the coating; dispersants, defoamers and leveling agents, as auxiliary components of the coating, each play an indispensable role. Dispersants can ensure that pigments and fillers are evenly dispersed in the coating, avoid agglomeration and precipitation, and ensure the uniformity and stability of the coating. Defoamers are used to eliminate bubbles during the preparation and construction of the coating to prevent bubbles from adversely affecting the appearance and performance of the coating. Leveling agents can improve the leveling of the coating, so that the coating forms a smooth and flat surface during the drying process, and improves the aesthetics and protective performance of the coating; low surface energy additives are a major feature of the coating of the present invention, which can significantly reduce the surface energy of the coating, so that the coating has excellent anti-fouling and self-cleaning properties. This feature allows the coating to be more easily washed off when it is contaminated, maintaining the long-term beauty and protective effect of the coating. Due to the use of low surface energy additives, the water contact angle of the coating of the present invention is greater than 120°, and it has good hydrophobic properties, which can effectively prevent the penetration of water and corrosive substances; deionized water, as a solvent for the coating, not only helps to disperse and dissolve the components, but also plays a role in adjusting the viscosity of the coating. An appropriate amount of deionized water can ensure the construction performance of the coating, make the coating easy to brush, spray or roll, and improve the construction efficiency and quality.
[0015] The invention forms a coating with excellent weather resistance, rust resistance, adhesion and low surface energy characteristics by proportioning various components. The coating can not only effectively protect the steel structure from corrosion and pollution, but also maintain the long-term beauty and stability of the coating.
[0016] The mass ratio of aqueous silica sol to acrylic resin in the present invention is (1-3): (7-9). The silica sol and the resin within this ratio range can form good mutual solubility and compatibility, ensuring that the coating has excellent comprehensive performance. The reinforcing effect of the silica sol and the film-forming performance of the resin complement each other, making the coating both hard and flexible, with good durability and aesthetics. Too high a silica sol content may make the coating too rigid, reducing flexibility and impact resistance; while too low a silica sol content may weaken the weather resistance and hardness of the coating. Therefore, it is crucial to reasonably control the ratio of aqueous silica sol to acrylic resin to obtain high-performance coatings.
[0017] The present invention prepares a modified anti-rust pigment, which combines physical anti-rust and chemical anti-rust. Micaceous iron oxide, as a physical anti-rust pigment, is famous for its unique lamellar structure and high chemical stability. In the coating, it can effectively block the direct contact between corrosive media such as moisture and oxygen and the steel structure, thereby delaying the corrosion process. At the same time, the lamellar structure of mica iron oxide can also enhance the physical barrier effect of the coating and improve the anti-penetration performance of the coating; aluminum tripolyphosphate, as an inorganic anti-rust pigment, has excellent corrosion inhibition performance. It can form a dense protective film with the surface of the steel structure, and this protective film can effectively inhibit the progress of the corrosion reaction. Aluminum tripolyphosphate in the coating undergoes chemical adsorption and complexation reaction with metal ions on the surface of the steel structure through its phosphate ions to form a stable protective film, and at the same time interacts with organic components such as acrylic resin to enhance the adhesion and anti-rust performance of the coating.
[0018] Bismuth molybdate is known for its excellent high temperature resistance and oxidation resistance. In coatings, it can effectively improve the thermal stability of the coating and prevent the coating from failing due to high temperature. At the same time, bismuth molybdate can also work synergistically with aluminum tripolyphosphate to enhance the anti-rust performance of the coating. Aluminum tripolyphosphate forms a dense passivation film on the surface of the steel structure through chelation, effectively inhibiting metal corrosion; while bismuth molybdate, with its excellent weather resistance and photocatalytic properties, not only enhances the overall stability of the coating, but also decomposes harmful substances under light conditions, further protecting the steel structure under the coating from erosion. The two complement each other and jointly improve the anti-rust performance and service life of the coating.
[0019] The mixed use of fluorocarbon resin and methacrylate resin provides excellent film-forming properties and adhesion for modified anti-rust pigments. Fluorocarbon resin is known for its excellent weather resistance, chemical resistance and low surface energy properties, which can effectively improve the durability and self-cleaning properties of the coating. Methacrylate resin is known for its good flexibility and processing properties, which helps to improve the construction performance of the coating and the bonding strength between coatings. The mixed use of fluorocarbon resin and methacrylate resin can combine the advantages of both. Fluorocarbon resin gives the coating excellent weather resistance, corrosion resistance and self-cleaning properties, while methacrylate resin provides good adhesion and processing properties. Compared with the use of one resin alone, the mixed use can significantly improve the overall performance of the coating, such as enhancing the hardness, gloss and chemical resistance of the coating, while broadening the application range of the coating, making it more suitable for complex and changeable steel structure surface protection.
[0020] During the preparation process, a mixture of mica iron oxide, aluminum tripolyphosphate and bismuth molybdate is dispersed in a mixture of fluorocarbon resin and methacrylate resin to form a uniform anti-rust pigment system. The addition of polyethylene glycol 2000 and silane coupling agent KH550 further enhances the interaction between the pigment particles and the resin matrix, and improves the dispersibility and stability of the pigment. As a dispersant, polyethylene glycol 2000 can effectively reduce the interaction between pigment particles and prevent pigment agglomeration; while silane coupling agent KH550 can form a chemical bond between the pigment particles and the resin matrix, enhancing the bonding strength between the two.
[0021] The low surface energy additive of the present invention can effectively reduce the free energy of the coating surface, so that the coating has excellent hydrophobic and oleophobic properties, thereby effectively preventing the adhesion of stains, moisture and other substances, and improving the self-cleaning and durability of the coating. By introducing fluorocarbon compounds, the additive can significantly improve the weather resistance and corrosion resistance of the coating, so that it can still maintain good appearance and performance in various harsh environments. The ingredients in the additive can work synergistically to improve key performance indicators of the coating such as leveling, adhesion and hardness, making the coating smoother, stronger and more durable.
[0022] Among the low surface energy additives, perfluoroalkyl ethanol and perfluoroalkyl acrylate are fluorocarbon compounds, which are the core components of low surface energy additives. They not only give the additives excellent low surface energy properties, but also form a dense fluorocarbon protective layer in the coating through their unique molecular structure, effectively isolating the erosion of the external environment. In the preparation process, the two substances are mixed in a mass ratio of 1:1, which provides a basis for subsequent reactions; as a modifier, hydrogen-containing fluorosilicone oil can enhance the compatibility and bonding between fluorocarbon compounds and the coating matrix, thereby improving the dispersibility and stability of the additive in the coating. It further enhances the low surface energy characteristics and weather resistance of the coating through interaction with components such as perfluoroalkyl acrylate; dimethyl sulfoxide, as a solvent, plays a role in dissolving and dispersing mixture C during the preparation process. It makes the reaction system more uniform, which is conducive to the subsequent polymerization reaction. At the same time, dimethyl sulfoxide also has a certain polarity, which helps to enhance the interaction between the additive and the coating matrix; ammonium persulfate plays a role in initiating the polymerization reaction during the preparation process. It is added dropwise to the reaction system at a certain rate, and undergoes free radical polymerization with perfluoroalkyl acrylate and other components to generate a high molecular compound with low surface energy characteristics. After the reaction process is initially stirred at room temperature, the temperature is slowly raised to 90-110°C and the reaction is kept at a constant temperature for 6-8 hours to ensure that the reaction is fully carried out.
[0023] During the preparation process, perfluoroalkylethanol and perfluoroalkylacrylate are first mixed evenly to form a basic mixture containing fluorocarbon segments. Hydrogen-containing fluorosilicone oil is then added for modification to enhance the compatibility and binding force of the additive. Mixture C is then dispersed in dimethyl sulfoxide to form a uniform solution system. Ammonium persulfate is slowly added dropwise as an initiator under stirring to initiate a free radical polymerization reaction of components such as perfluoroalkylacrylate. This reaction process forms a chemical bond connection between the fluorocarbon segment and the resin matrix, thereby generating a polymer compound with excellent low surface energy properties and weather resistance. Finally, the low surface energy additive is obtained by steps such as standing and cooling.
[0024] In the base material preparation stage, the present invention combines low-speed pre-stirring and high-speed dispersion treatment, so that various raw materials can be fully mixed and achieve an extremely fine dispersion effect (fineness <30μm), improve the uniformity and stability of the coating, ensure the quality of the coating, and after adding the aqueous silica sol, through appropriate stirring rate and time control, make it fully blended with the base material, then add acrylic resin, leveling agent and low surface energy additive, and continue to stir, ensure the uniform distribution of all components in the coating, thereby improving the overall performance of the coating. The coating prepared by the method has low surface energy characteristics, can effectively reduce the adhesion of stains, moisture and other substances, and improve the self-cleaning and durability of the coating. At the same time, the addition of modified anti-rust pigments enhances the anti-rust performance of the coating, making the coating more durable. The raw materials used in the entire preparation process are all water-based materials, and low VOC emissions meet environmental protection requirements. This not only helps to protect the health of construction workers, but also reduces the impact on the environment. The coating has good recoatability and is convenient for multi-layer coating on the surface of steel structures to meet the requirements of corrosion protection and beauty in different occasions and needs.
[0025] The coating prepared by the present invention has good compatibility with a variety of old coatings, and can be re-coated with common steel structure coatings such as epoxy coatings, polyurethane coatings, and alkyd coatings. Before re-coating, there is no need to completely remove the old coating, and it is only necessary to ensure that the surface is clean and dry. This is mainly because the film-forming substances and additives in the coating can interact with the old coating to form good adhesion. Specifically, the silicon-oxygen bonds (Si-O) in the aqueous silica sol hybrid acrylic resin and the functional groups in the acrylic resin can form chemical bonds or hydrogen bonds with the polar groups in the old coating, thereby achieving good bonding. At the same time, the presence of low surface energy additives also helps to reduce the surface tension difference between the coating and the old coating, thereby improving the compatibility of the two.
[0026] The coating prepared by the present invention can be re-coated by various coating methods, such as spraying, brushing or rolling. The viscosity and thickness of the coating are controlled to ensure uniform coating. Generally, the thickness of each coating is controlled between 50 and 100 μm, and multiple coatings can be applied as needed to achieve the desired anticorrosion effect.
[0027] The aqueous silica sol in the present invention was purchased from Hubei Changfu Chemical Co., Ltd.; the acrylic resin in the present invention was purchased from Shanghai Haohong Biomedical Technology Co., Ltd. with a purity of 99%; the mica iron oxide in the present invention was purchased from Wuhan Jiyesheng Chemical Co., Ltd. with a purity of 99.9%; the aluminum tripolyphosphate in the present invention was purchased from Wuhan Jiyesheng Chemical Co., Ltd. with a purity of 98%; the bismuth molybdate in the present invention was purchased from Ningbo Chemical Raw Materials Co., Ltd. with a purity of 99%; the fluorocarbon resin in the present invention was purchased from Chengdu Keguan Paint Co., Ltd. with a purity of 90%; the methacrylic resin in the present invention was purchased from Shandong Chuangying Chemical Co., Ltd. with a purity of 99.5%; the perfluoroalkylethanol in the present invention was purchased from Jinan Xinrun Technology Development Co., Ltd. with a purity of 95%; the perfluoroalkylacrylate in the present invention was purchased from Wuhan Kemik Biomedical Technology Co., Ltd. with a purity of 95%; the hydrogen-containing fluorosilicone oil in the present invention was purchased from Hunan Jiahang Pharmaceutical Technology Co., Ltd. with a purity of 99%.
[0028] Beneficial effects of the present invention: The coating prepared by the present invention uses a low surface energy additive, and the water contact angle of the prepared coating is greater than 120°, and the coating has good hydrophobicity, and can effectively prevent the penetration of moisture and corrosive substances; the coating can be well combined with a variety of old coatings, and can be directly re-coated without complicated treatment of the steel structure surface, thereby improving construction efficiency and reducing maintenance costs; the synergistic effect of the film-forming substance and the anti-rust pigment makes the coating have excellent anti-corrosion performance, and can effectively extend the service life of the steel structure. DETAILED DESCRIPTION
[0029] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0030] Example 1 A water-based recoatable low surface energy coating for the surface of a steel structure, wherein the coating formula is as follows: by weight, 20 parts of water-based silica sol, 80 parts of acrylic resin, 20 parts of modified anti-rust pigment, 2 parts of hydroxymethyl cellulose, 0.5 parts of diethanolamine, 1 part of GLIDE 450W, 1 part of low surface energy additive, and 20 parts of deionized water; Among them, the mass ratio of aqueous silica sol to acrylic resin is 2:9; The specific preparation method of the modified anti-rust pigment is as follows: S2.1: Micaceous iron oxide, aluminum tripolyphosphate and bismuth molybdate are mixed in a mass ratio of 1:1:1, and ground in a ball mill at a speed of 400 r / min for 1 h to obtain a mixture A, wherein the particle size of the mixture A is 400 mesh; S2.2: fluorocarbon resin and methacrylic resin were mixed in a volume ratio of 2:1, and stirred at a speed of 200 r / min for 0.5 h to obtain a mixed resin B; S2.3: Disperse mixture A in mixed resin B with a solid-liquid mass ratio of 1:2, stir at a speed of 400 r / min for 0.5 h, then add 1 wt% polyethylene glycol 2000 and 1 wt% silane coupling agent KH550, continue stirring for 0.5 h, filter the mixture using a 300 mesh gauze to obtain the modified anti-rust pigment.
[0031] The low surface energy additive preparation method is as follows: Under stirring at a speed of 200 r / min, perfluoroalkylethanol and perfluoroalkylacrylate are mixed in a mass ratio of 1:1, 3wt% of hydrogen-containing fluorosilicone oil is added to the mixture to obtain a mixture C, and the mixture C is dispersed in dimethyl sulfoxide, the volume ratio of the mixture C to dimethyl sulfoxide is 1:2, and stirring is continued. While stirring, ammonium persulfate is slowly added at a rate of 2s / drop, wherein the mass ratio of the added ammonium persulfate to the perfluoroalkylacrylate is 1:20. After the addition is completed, stirring is continued at room temperature for 10 minutes, and then the temperature is slowly increased to 110°C at 2°C / min under stirring, and the reaction is carried out for 6 hours after the constant temperature. After the reaction is completed, the mixture is allowed to stand and the temperature is cooled to room temperature to obtain the low surface energy additive.
[0032] The specific process of the preparation method of the water-based recoatable low surface energy coating is as follows: S9.1: Add deionized water to a dispersion tank, add dispersant, defoamer and modified anti-rust pigment in order according to the formula ratio under stirring at a speed of 300 r / min, stir for 10 minutes, and then perform high-speed dispersion treatment at a speed of 2000 r / min for 20 minutes to obtain a base material with a base material fineness of <30 μm; S9.2: Slowly add the aqueous silica sol to the base material, stir at a speed of 300 r / min, stir for 20 minutes, add acrylic resin, leveling agent and low surface energy additive, continue stirring for 2 hours, and obtain the aqueous recoatable low surface energy coating.
[0033] Example 2 A water-based recoatable low surface energy coating for the surface of a steel structure, wherein the coating formula is as follows: by weight, 10 parts of water-based silica sol, 70 parts of acrylic resin, 10 parts of modified anti-rust pigment, 1 part of polyethylene oxide, 0.1 parts of isopropanol, 0.5 parts of GLIDE450W, 0.5 parts of low surface energy additive, and 10 parts of deionized water; Among them, the mass ratio of aqueous silica sol to acrylic resin is 1:7; The specific preparation method of the modified anti-rust pigment is as follows: S2.1: Micaceous iron oxide, aluminum tripolyphosphate and bismuth molybdate are mixed in a mass ratio of 1:1:0.5, and ground in a ball mill at a speed of 400 r / min for 0.5 h to obtain a mixture A, wherein the particle size of the mixture A is 400 mesh; S2.2: fluorocarbon resin and methacrylic resin were mixed in a volume ratio of 2:1, and stirred at a speed of 200 r / min for 0.5 h to obtain a mixed resin B; S2.3: Disperse mixture A in mixed resin B with a solid-liquid mass ratio of 1:2, stir at a speed of 400 r / min for 0.5 h, then add 1 wt% polyethylene glycol 2000 and 1 wt% silane coupling agent KH550, continue stirring for 0.5 h, filter the mixture using a 300 mesh gauze to obtain the modified anti-rust pigment.
[0034] The low surface energy additive preparation method is as follows: Under stirring at a speed of 200 r / min, perfluoroalkylethanol and perfluoroalkylacrylate are mixed in a mass ratio of 1:1, 3wt% of hydrogen-containing fluorosilicone oil is added to the mixture to obtain a mixture C, and the mixture C is dispersed in dimethyl sulfoxide, the volume ratio of the mixture C to dimethyl sulfoxide is 1:2, and stirring is continued. While stirring, ammonium persulfate is slowly added at a rate of 2s / drop, wherein the mass ratio of the added ammonium persulfate to the perfluoroalkylacrylate is 1:20. After the addition is completed, stirring is continued at room temperature for 10 minutes, and then the temperature is slowly increased to 90°C at 2°C / min under stirring, and the reaction is carried out for 8 hours after the constant temperature. After the reaction is completed, the mixture is allowed to stand and the temperature is cooled to room temperature to obtain the low surface energy additive.
[0035] The specific process of the preparation method of the water-based recoatable low surface energy coating is as follows: S9.1: Add deionized water to a dispersion tank, add dispersant, defoamer and modified anti-rust pigment in order according to the formula ratio under stirring at a speed of 300 r / min, stir for 10 minutes, and then perform high-speed dispersion treatment at a speed of 1500 r / min for 20 minutes to obtain a base material with a base material fineness of <30 μm; S9.2: Slowly add the aqueous silica sol into the base material, stir at a speed of 300 r / min, stir for 10 minutes, add acrylic resin, leveling agent and low surface energy additive, continue stirring for 1 hour, and obtain the aqueous recoatable low surface energy coating.
[0036] Example 3 A water-based recoatable low surface energy coating for the surface of a steel structure, wherein the coating has the following formula, by weight, 30 parts of water-based silica sol, 90 parts of acrylic resin, 20 parts of modified anti-rust pigment, 2 parts of polyvinyl alcohol, 0.3 parts of lauroyl isopropanolamine, 0.5 parts of GLIDE 411, 1 part of low surface energy additive, and 20 parts of deionized water; Among them, the mass ratio of aqueous silica sol to acrylic resin is 3:9; The specific preparation method of the modified anti-rust pigment is as follows: S2.1: Micaceous iron oxide, aluminum tripolyphosphate and bismuth molybdate are mixed in a mass ratio of 1:1:1, and ground in a ball mill at a speed of 400 r / min for 1 h to obtain a mixture A, wherein the particle size of the mixture A is 400 mesh; S2.2: fluorocarbon resin and methacrylic resin were mixed in a volume ratio of 2:1, and stirred at a speed of 200 r / min for 0.5 h to obtain a mixed resin B; S2.3: Disperse mixture A in mixed resin B with a solid-liquid mass ratio of 1:2, stir at a speed of 400 r / min for 0.5 h, then add 1 wt% polyethylene glycol 2000 and 1 wt% silane coupling agent KH550, continue stirring for 0.5 h, filter the mixture using a 300 mesh gauze to obtain the modified anti-rust pigment.
[0037] The low surface energy additive preparation method is as follows: Under stirring at a speed of 200 r / min, perfluoroalkylethanol and perfluoroalkylacrylate are mixed in a mass ratio of 1:1, 3wt% of hydrogen-containing fluorosilicone oil is added to the mixture to obtain a mixture C, and the mixture C is dispersed in dimethyl sulfoxide, the volume ratio of the mixture C to dimethyl sulfoxide is 1:2, and stirring is continued. While stirring, ammonium persulfate is slowly added at a rate of 2s / drop, wherein the mass ratio of the added ammonium persulfate to the perfluoroalkylacrylate is 1:20. After the addition is completed, stirring is continued at room temperature for 10 minutes, and then the temperature is slowly increased to 110°C at 2°C / min under stirring, and the reaction is carried out for 6 hours after the constant temperature. After the reaction is completed, the mixture is allowed to stand and the temperature is cooled to room temperature to obtain the low surface energy additive.
[0038] The specific process of the preparation method of the water-based recoatable low surface energy coating is as follows: S9.1: Add deionized water to a dispersion tank, add dispersant, defoamer and modified anti-rust pigment in order according to the formula ratio under stirring at a speed of 300 r / min, stir for 10 minutes, and then perform high-speed dispersion treatment at a speed of 2000 r / min for 20 minutes to obtain a base material with a base material fineness of <30 μm; S9.2: Slowly add the aqueous silica sol into the base material, stir at a speed of 300 r / min, stir for 10 minutes, add acrylic resin, leveling agent and low surface energy additive, continue stirring for 1 hour, and obtain the aqueous recoatable low surface energy coating.
[0039] Comparative Example 1 In this comparative example, no mica iron oxide is added in the preparation of the modified anti-rust pigment, and the remaining steps are consistent with those of Example 1.
[0040] Comparative Example 2 In this comparative example, aluminum tripolyphosphate is not added in the preparation of the modified anti-rust pigment, and the remaining steps are consistent with those of Example 1.
[0041] Comparative Example 3 In this comparative example, bismuth molybdate is not added in the preparation of the modified anti-rust pigment, and the remaining steps are consistent with those in Example 1.
[0042] Comparative Example 4 In this comparative example, no fluorocarbon resin is added in the preparation of the modified anti-rust pigment, and the remaining steps are consistent with those of Example 1.
[0043] Comparative Example 5 In this comparative example, no methacrylic acid resin is added in the preparation of the modified anti-rust pigment, and the remaining steps are consistent with those of Example 1.
[0044] Comparative Example 6 In this comparative example, no perfluoroalkylethanol is added in the preparation of the low surface energy additive, and the remaining steps are consistent with those of Example 1.
[0045] Comparative Example 7 In this comparative example, no hydrogen fluorine silicone oil is added in the preparation of the low surface energy additive, and the remaining steps are consistent with those of Example 1.
[0046] Comparative Example 8 In this comparative example, the mass ratio of aqueous silica sol to acrylic resin is 1:10, and the remaining steps are consistent with Example 1.
[0047] Comparative Example 9 In this comparative example, the mass ratio of aqueous silica sol to acrylic resin is 1:1, and the remaining steps are consistent with Example 1.
[0048] The performance of the examples and comparative examples was tested. The prepared coatings were coated on steel plates with a thickness of 50 μm. 1. Water contact angle test: Tested in accordance with GB / T 30693-2014 "Measurement of contact angle between plastic film and water" standard; 2. Adhesion test: Test according to GB / T 9286-1998 "Scratch test for paint and varnish film" standard; 3. Salt spray resistance test: Test according to GB / T 1771-2007 "Determination of neutral salt spray resistance of paints and varnishes". After 1000 hours of salt spray test, observe the changes in the appearance of the sample; 4. Weather resistance test: Place the coating sample in an outdoor natural environment for exposure test. After 1 year of exposure, observe the appearance color of the sample; The test results are summarized in the following table:
[0049] It can be seen from the above experimental results that the low surface energy additive prepared by the present invention enables the coating to have better hydrophobic properties; the modified anti-rust pigment prepared by the present invention enables the coating to have better anti-rust properties; the limitation of the mass ratio of aqueous silica sol to acrylic resin by the present invention enables the prepared coating to have better tolerance and adhesion.
[0050] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A water-based recoatable low surface energy coating for steel structure surface, characterized in that: The coating formula is as follows: by weight, 10-30 parts of aqueous silica sol, 70-90 parts of acrylic resin, 10-20 parts of modified anti-rust pigment, 1-2 parts of dispersant, 0.1-0.5 parts of defoamer, 0.5-1 parts of leveling agent, 0.5-1 parts of low surface energy additive, and 10-20 parts of deionized water; Wherein, the mass ratio of aqueous silica sol to acrylic resin is (1-3): (7-9); The modified anti-rust pigment is prepared by dispersing mica iron oxide, aluminum tripolyphosphate and bismuth molybdate in a fluorocarbon resin and a methacrylic resin in a volume ratio of 2:1; The low surface energy auxiliary agent is prepared by mixing perfluoroalkyl ethanol, perfluoroalkyl acrylate, hydrogen-containing fluorinated silicone oil, dimethyl sulfoxide and ammonium persulfate.
2. The water-based recoatable low surface energy coating for steel structure surface according to claim 1, characterized in that: The specific preparation method of the modified anti-rust pigment is as follows: S2.1: Micaceous iron oxide, aluminum tripolyphosphate and bismuth molybdate are mixed in a mass ratio of 1:1:(0.5-1), and ground in a ball mill at a speed of 400 r / min for 0.5-1 h to obtain a mixture A; S2.2: fluorocarbon resin and methacrylic resin were mixed in a volume ratio of 2:1, and stirred at a speed of 200 r / min for 0.5 h to obtain a mixed resin B; S2.3: Disperse mixture A in mixed resin B with a solid-liquid mass ratio of 1:2, stir at a speed of 400 r / min for 0.5 h, then add 1 wt% polyethylene glycol 2000 and 1 wt% silane coupling agent KH550, continue stirring for 0.5 h, filter the mixture with a gauze to obtain the modified anti-rust pigment.
3. The water-based recoatable low surface energy coating for steel structure surface according to claim 1, characterized in that: The dispersant is one or more of hydroxymethyl cellulose, polyethylene oxide, and polyvinyl alcohol.
4. The water-based recoatable low surface energy coating for steel structure surface according to claim 1, characterized in that: The defoaming agent is one or more of diethanolamine, isopropanol, and lauroyl isopropanolamine.
5. The water-based recoatable low surface energy coating for steel structure surface according to claim 1, characterized in that: The leveling agent is one of GLIDE 450W and GLIDE 411.
6. The water-based recoatable low surface energy coating for steel structure surface according to claim 1, characterized in that: The low surface energy additive preparation method is as follows: Under stirring at a speed of 200 r / min, perfluoroalkylethanol and perfluoroalkylacrylate are mixed in a mass ratio of 1:1, 3wt% of hydrogen-containing fluorosilicone oil is added to the mixture to obtain a mixture C, and the mixture C is dispersed in dimethyl sulfoxide, the volume ratio of the mixture C to dimethyl sulfoxide is 1:2, and stirring is continued. While stirring, ammonium persulfate is slowly added at a rate of 2s / drop, wherein the mass ratio of the added ammonium persulfate to the perfluoroalkylacrylate is 1:
20. After the addition is completed, stirring is continued at room temperature for 10 minutes, and then the temperature is slowly increased to 90-110°C at 2°C / min under stirring, and the reaction is carried out for 6-8 hours after the constant temperature. After the reaction is completed, the mixture is allowed to stand and the temperature is cooled to room temperature to obtain the low surface energy additive.
7. The water-based recoatable low surface energy coating for steel structure surface according to claim 2, characterized in that: The particle size of the mixture A in S2.1 is 400 mesh.
8. The water-based recoatable low surface energy coating for steel structure surface according to claim 2, characterized in that: In the S2.3, a 300-mesh gauze is used for filtering.
9. A method for preparing a water-based recoatable low surface energy coating for a steel structure surface, based on the water-based recoatable low surface energy coating for a steel structure surface according to any one of claims 1 to 8, characterized in that: The specific process of the preparation method of the water-based recoatable low surface energy coating is as follows: S9.1: Add deionized water into a dispersion tank, add dispersant, defoamer and modified anti-rust pigment in order according to the formula ratio under stirring at a speed of 300 r / min, stir for 10 minutes, and then perform high-speed dispersion treatment at a speed of 1500-2000 r / min for 20-30 minutes to obtain a base material; S9.2: Slowly add the aqueous silica sol to the base material, stir at a speed of 300 r / min, stir for 10 to 20 minutes, add acrylic resin, leveling agent and low surface energy additive, continue stirring for 1 to 2 hours, and obtain the aqueous recoatable low surface energy coating.
10. The method for preparing a water-based recoatable low surface energy coating for a steel structure surface according to claim 9, characterized in that: The fineness of the base material dispersed in S9.1 is less than 30 μm.
Citation Information
Patent Citations
Perfluoro alkyl ethyl acrylic ester-modified single-component acrylic resin and preparation method as well as application thereof
CN102250280A
Modified water-based inorganic zinc rich coating and preparation method thereof
CN103305041A
Application of nano silicon dioxide sol in water-based steel structure anticorrosive paint and protective paint
CN103937353A
Solar panel light conversion coating with air-purifying and self-cleaning functions
CN107384054A
Water industrial paint based on organosilicon acrylic acid epoxy ester water dispersion and preparation method thereof
CN1927968A
Cited By
Corrosion-resistant coating for color-coated aluminum plate strip and preparation method of corrosion-resistant coating
CN121718230A
Corrosion-resistant coating for color-coated aluminum plate strip and method for preparing the same
CN121718230B